Syndrome of Accumulation of Air and Fluid in the Pleural Space (Pleurisy, Hydrothorax, Pneumothorax), Shortness of Breath, Diagnostics, General Understanding of Etiology and Pathogenesis - Murodullayev Bekjon Nurali oʻgʻli; Sagdullayeva Dilsoʻz Rahim qizi; Abdullayeva Nasiba Boboraxim qizi; Rabbimov Muhammad Ali Qarshiboyevich; Davlatova Durdona O'tkir qizi; Жумагелдиев Умиджон Эрали угли (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article delves into the information about Syndrome of accumulation of air and fluid in the pleural space (pleurisy, hydrothorax, pneumothorax), shortness of breath and its diagnostics, as well as General understanding of etiology and pathogenesis.